Children, Sexuality, and the Law - Marrus, Ellen; Coupet, Sacha M. (Book collections on Project MUSE., 2015)
American political and legal culture is uncomfortable with children's sexuality. While aware that sexual expression is a necessary part of human development, law rarely contemplates the complex ways in which it interacts with children and sexuality. Just as the law circumscribes children to a narrow range of roles-either as entirely sexless beings or victims or objects of harmful adult sexual conduct-so too does society tend to discount the notion of children as agents in the domain of sex and sexuality. Where a small body of rights related to sex has been carved out, the central question has.